Synthesis of new aryl(hetaryl)-substituted tandospirone analogues with potential anxiolytic activity via reductive Heck type hydroarylations - Gunkara, Omer Tahir; Sucu, Bilgesu Onur; Ocal, Nuket; Kaufmann, Dieter E. (VERSITA, 2013)
Tandospirone (I), developed as an anxiolytic drug, is an aryl-piperazine compound that binds to both 5-HT1A and dopamine D4 receptors. Palladium-catalysed hydroarylation reactions of tandospirone analogues containing an oxygen bridge and 3-(trifluoromethyl)phenyl or 2,3-dichlorophenyl groups were studied in order to find a new stereoselective access to a series of new exo-aryl(hetaryl)-substituted derivatives with potential biological activity.
Keywords: tandospirone; arylpiperazines; C-C coupling; hydroarylation; heterocycles; SUBSTITUTED TRICYCLIC IMIDES; DOPAMINE D3 RECEPTOR; UNSATURATED DICARBOXIMIDES; PHARMACOLOGICAL AGENTS; EPIBATIDINE; DERIVATIVES; CHEMISTRY; AFFINITY; NUCLEUS; AGONIST